1969
DOI: 10.1128/aem.18.2.142-146.1969
|View full text |Cite
|
Sign up to set email alerts
|

Medical Applications of Dust-free Rooms. III. Use in an Animal Care Laboratory

Abstract: Bacterial air sampling in an animal care laboratory showed that dense aerosols are generated during cage changing and cage cleaning. Reyniers and Andersen sampling showed that the airborne bacteria numbered 50 to 200 colony-forming units (CFU)/ft3 of air. Of the viable particles collected by Andersen samplers, 78.5% were larger than 5.5 ,m. A low velocity laminar air flow system composed of high-efficiency particulate air (HEPA) filters and a ceiling distribution system maintained the number of airborne viable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The vertical air velocity used in this hood (19 cm/s) is substantially lower than that conventionally employed in laminar air flow systems (50 cm/s), but we have shown that lowered air velocities are effective in elimination of airborne contamination in tissue culture laboratories and operating rooms and elimination of airborne infection in animal laboratories in controlled studies (5,7,11,12).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The vertical air velocity used in this hood (19 cm/s) is substantially lower than that conventionally employed in laminar air flow systems (50 cm/s), but we have shown that lowered air velocities are effective in elimination of airborne contamination in tissue culture laboratories and operating rooms and elimination of airborne infection in animal laboratories in controlled studies (5,7,11,12).…”
Section: Resultsmentioning
confidence: 89%
“…This restriction of infectious foci inside the cabinet may be due to the unidirectional air flow and the absence of bedding. We have previously demonstrated how these two factors can inluence spread of airborne infection (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation